Predatory behavior and predation efficiency of Sycanus sp. against Metisa plana Walker: Implications for biological control in oil palm: Perilaku pemangsaan dan efisiensi predasi Sycanus sp. terhadap Metisa plana Walker: Implikasinya terhadap pengendalian hayati pada kelapa sawit - Zahlul Ikhsan; Mona Aisyah; Nalwida Rozen; Sri Heriza; Moustafa Sabry Bakry; Amsar Maulana; Nur Ain Izzati Mohd Zainudin (Jurnal Entomologi Indonesia, 2026)
Bagworm (Metisa plana Walker) is a major defoliating pest of oil palm, causing significant yield losses during outbreaks. Biological control using predatory insects offers an environmentally sustainable alternative to chemical insecticides. This study evaluated the predatory performance of Sycanus sp. against M. plana larvae and assessed the effect of predator density on prey suppression under laboratory conditions. A completely randomized design was used with five predator-density treatments (1, 2, 3, 4, and 5 predators per 10 larvae) and ten replications. Predator performance was evaluated based on prey-search duration, handling time, larval mortality, and prey consumption. The initial prey-search duration ranged from 2.11 to 2.25 min, while subsequent searches ranged from 1.69 to 2.04 min. Prey-handling time remained relatively constant across treatments (58.1–59.1 min). Predation by Sycanus sp. substantially reduced M. plana populations within three days, with the highest mortality occurring on the first day after predator introduction. Predator density significantly increased prey consumption, which rose from 1.26 ± 0.21 larvae at one predator to 4.43 ± 0.19 larvae at five predators. A strong positive relationship was observed between predator density and prey consumption (y = 0.795x + 0.451; R² = 0.9531). Although the highest prey suppression occurred at the greatest predator density, a ratio of two Sycanus sp. adults per ten M. plana larvae provided a favorable balance between prey suppression and predator deployment efficiency. These findings support the potential use of Sycanus sp. as a biological control agent in sustainable oil palm integrated pest management programs.